Efektivitas Metode Suggestopedia dalam Meningkatkan Maharah Istima' - Ismail, Ismail; Taubah, Miftachul; Syarifuddin, Syarifuddin (‘A Jamiy : Jurnal Bahasa dan Sastra Arab, 2025)
This study aims to determine the effectiveness of suggestopedia method in improving maharah istima' of junior high school students. The research was conducted with a quantitative approach using a one-group pretest-posttest pre-experiment design. Data were collected through observation, interviews with teachers and students, and tests to measure changes in maharah istima' before and after the application of the suggestopedia method. The results of data analysis showed a significant increase in students' maharah istima' ability after the application of the suggestopedia method. Statistical tests showed a significant difference between pretest scores with an average value of 42.24 and posttest 46.56. The findings of this study state that the suggestopedia method is effective in improving students' maharah istima' in Arabic language learning. The implication of this study shows the potential of suggestopedia method as one of the methods that can be adopted to improve Arabic language learning especially maharah istima'.